Podejście infologiczne w doskonaleniu jakości informacji - Gryncewicz, Wiesława (Infological Approach in Information Quality Improvement, 2007)
Information of high quality is required for optimal business performance. The aim of this article is to present an information quality improvement model, which bases on the infological approach. There are quantitative and qualitative theories of information. Infological approach is one of the most interesting directions in scientific research in qualitative theory of information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 158-168